Meta-awareness of university students - Akram Khalaf Sajit; Dr. Salam Ghayyad (Journal of College of Education, 2023)
The aim of the current study is to identify:1- The meta-conscious level of university students,2- Significance of differences in meta-consciousness among university students (scientific - humanitarian specialization) according to gender variables (male - female).The current study community was identified as the students of Wasit University for morning studies for the academic year (2021-2022), who numbered (13940), with (7752) male and female students from scientific disciplines and (6188) male and female students from human specialties, and the current research sample included (400) students.  A student from Wasit University, and after reviewing the literature and previous studies, the researcher adopted the researcher adopted a scale beyond  Consciousness (Falafel, 1979), which consists of (30) items, They were presented to experts and specialists to judge their validity, and then the researcher applied the standards to the research sample. After completing the application, the researcher used the appropriate statistical methods to analyze the data, and the research showed the following results:1- Wasit University students enjoy a good measure of meta-consciousness that enables them to face stressful life events within the academic institution represented by the university.2- There are no differences in meta-consciousness among university students according to the gender variable (males, females), while it became clear to us that there are statistically significant differences in meta-consciousness in favor of the scientific specialization according to the academic specialization (scientific, human).
Keywords: Al-Majashi, the weightings, the opinions presented